The Ontology of Government Studies Development: A Systematic Review - Tri Sulistyaningsih; Muhammad Kamil; Umi Kulsum; Eko Priyo Purnomo; Salahudin Salahudin; Ali Roziqin (Department of Government Studies Universitas Muhammadiyah Makassar, 2022)
Ontology is the process of discussing knowledge from a philosophical point of view. Therefore, this research aims to explain the nature of government studies based on ontology, which is a governmental science used to carry out periodic paradigm shifts. Data was collected from the Scopus database and reviewed using the systematic method. The results showed that government studies are associated with the management of the executive and legislative branches, their leadership, and the relationship between central and local government and between government and society. The study of government science progress is in three phases; the first determines the essence of science in governance and ends with the third phase, which is the development of the concept of good governance. The governance concept is considered a solution to the crisis of lack of public trust in the government and their participation, effectiveness, accountability, and coherence in community activities. This becomes the wheels of government by mono and multi-stakeholder. Collaborative correlation is the initiation by the government to involve the public and the private sector.